Applicability of the UK DCD risk score in the modern era of liver transplantation: A U.S. update. Issue 4 (11th January 2022) - Wu, W. Kelly; Ziogas, Ioannis A.; Matsuoka, Lea K.; Izzy, Manhal; Alexopoulos, Sophoclis P.
Abstract: Background: Careful graft and recipient selection have resulted in improved outcomes in liver transplantation (LT) using donation after cardiac death (DCD) organs. The UK DCD Risk Score was established as a risk stratification tool to guide selection. Methods: We evaluated the applicability of the UK DCD Risk Score in a contemporary US cohort of adult DCD LT recipients using the United Network for Organ Sharing registry (2011‐2020). Results: A total of 3, 899 DCD LTs were included in our study (UK DCD Risk Score 0–5 points: 1, 438 [36.9%], 6–10 points: 2, 034 [52.2%]; 11–20 points: 427 [11.0%]). Compared to a score of 6–10 points, a score of 0–5 points was associated with decreased risk of graft loss (HR = .79, 95%CI: .68‐.93, p  = .004), while a score of 11–20 points was associated with increased risk of graft loss (HR = 1.26, 95%CI: 1.01‐1.56, p  = .04). The 5‐year graft survival for patients with risk scores of 0–5, 6–10, and 11–20 were 75.9%, 71.8%, and 66.5%, respectively. The C‐statistic for the UK DCD Risk Score in our contemporary cohort was .611. Conclusions: The UK DCD Risk Score demonstrates a more limited ability to differentiate recipient outcomes in the modern era of DCD LT in the US. Acceptable long‐term outcomes are achievable for patients stratified to the highest‐risk group.